Polypropylene resin composition and molded product
Through the combination of polypropylene polymer and biomass filler of a specific proportion, the problem of reduced flowability and color change of polypropylene resin caused by biomass filler is solved, and injection molded products with high fluidity and good appearance are achieved.
Patent Information
- Application Number
- JP2024120417
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-27
- Filing Date
- 2024-07-25
- Publication Date
- 2025-02-06
AI Technical Summary
In the prior art, biomass fillers are prone to reduce the liquidity of the resin and problems with the surface conditions and shape of the molded product in polypropylene resin. At the same time, the color change of the biomass fillers leads to the poor appearance of the molded product.
Using a specific proportion of polypropylene polymer and biomass filler, the fluidity of the resin and the dispersion of the biomass filler are improved and color change is reduced by using a compatible agent and a biomass filler of a specific particle size, and the polypropylene resin composition with a specific melt flow rate and viscosity.
The polypropylene resin composition is achieved without discoloration during injection molding, and has good fluidity and appearance quality.
Smart Images

Figure 2025019032000001 
Figure 2025019032000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polypropylene resin composition containing a biomass filler and a molded article thereof. More specifically, the present invention relates to a polypropylene resin composition that is less susceptible to discoloration due to fading of the biomass filler during injection molding and has excellent appearance and a molded article thereof. [Background technology]
[0002] Polypropylene is widely used for various applications such as various industrial materials, automobile-related parts, various containers for medical and cosmetic use, daily necessities, films and fibers due to its excellent heat resistance, moldability, transparency and chemical resistance. Meanwhile, in recent years, with the growing demand for the construction of a recycling-oriented society, there is a desire to move away from fossil fuels in the materials field as well as in energy, and the use of biomass has been attracting attention. Biomass is an organic compound photosynthesized from carbon dioxide and water, and by using it, it is converted back into carbon dioxide and water, making it a so-called carbon-neutral renewable energy. Recently, studies on the practical application of resin compositions derived from these biomasses have been rapidly progressing, and for example, studies on adding biomass fillers to polypropylene (Patent Documents 1 and 2) have been carried out.
[0003] On the other hand, biomass fillers often contain polar groups. For example, cellulose has many hydroxyl groups and is prone to aggregation due to intermolecular hydrogen bonds. In addition, it has low affinity with non-polar resins such as polyethylene and polypropylene, so attempts have been made to disperse cellulose in resins. For example, Patent Document 3 discloses a production method in which a master batch obtained by kneading a polyamide resin with cellulose nanofiber is kneaded with a polyolefin resin.
[0004] Furthermore, when a large amount of biomass filler is present in a resin, the fluidity of the resin decreases, causing defects in the surface condition and shape of the molded product. For example, Patent Document 4 discloses a composite material consisting of a specific wax, biomass filler, and polypropylene. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] WO03 / 070824 publication [Patent Document 2] JP 2023-91719 A [Patent Document 3] JP 2023-11541 A [Patent Document 4] JP 2011-236410 A Summary of the Invention [Problem to be solved by the invention]
[0006] The problem to be solved by the present invention is to provide a polypropylene resin composition and a molded article thereof which are less susceptible to discoloration due to fading of a biomass filler and have excellent moldability and molded appearance, in view of the current state of the prior art. [Means for solving the problem]
[0007] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that a polypropylene resin composition containing a specific propylene-based polymer (A) can solve the above problems. Based on these findings, the present invention has been completed.
[0008] That is, according to the first aspect of the present invention, there is provided a polypropylene resin composition comprising 0.5 to 20 parts by weight of a compatibilizer (C) and 3 to 150 parts by weight of a biomass filler (D) relative to 100 parts by weight of a polypropylene composition (X) satisfying the following requirement (Xi), and having a melt flow rate (MFR: 230°C, 2.16 kg load) of 10 to 100 g / 10 min. Requirement (Xi): The polypropylene composition (X) contains a propylene polymer (A) that satisfies the following requirements (Ai) to (A-ii). Requirement (Ai): The propylene polymer (A) contains a propylene / α-olefin block copolymer (A1) which satisfies the following requirements (A1-i) to (A1-iii): Requirement (A1-i): The propylene / α-olefin block copolymer (A1) contains a propylene homopolymer portion (a1-1) and a propylene / α-olefin copolymer portion (a1-2), and the propylene homopolymer portion (a1-1) is 50 to 95% by weight and the propylene / α-olefin copolymer portion (a1-2) is 5 to 50% by weight (however, the total of the propylene homopolymer portion (a1-1) and the propylene / α-olefin copolymer portion (a1-2) is 100% by weight). Requirement (A1-ii): The propylene content of the propylene-α-olefin copolymer part (a1-2) is 30 to 80% by weight, and the α-olefin content is 20 to 70% by weight (with the proviso that the total of the propylene content and the α-olefin content is 100% by weight). Requirement (A1-iii): The intrinsic viscosity [η] of the propylene-α-olefin copolymer portion (a1-2) measured in o-dichlorobenzene at 135°C is 7.0 to 12.0 dl / g or less. Requirement (A-ii): The propylene polymer (A) has a melt flow rate (230° C., 2.16 kg load) of 1.0 to 200 g / 10 min.
[0009] The second aspect of the present invention provides the polypropylene resin composition according to the first aspect of the present invention, wherein the propylene-α-olefin block copolymer (A1) is at least one selected from the group consisting of a propylene-ethylene block copolymer and a propylene-ethylene-1-butene block copolymer.
[0010] In addition, according to a third aspect of the present invention, there is provided a polypropylene resin composition according to the first or second aspect of the present invention, wherein the polypropylene composition (X) further contains a propylene polymer (B) satisfying the following requirements (Bi) to (B-iii) and further satisfies the following requirement (X-ii): Requirement (Bi): The propylene polymer (B) is a propylene-α-olefin block copolymer containing a propylene homopolymer portion (b-1) and a propylene-α-olefin copolymer portion (b-2). Requirement (B-ii): The propylene polymer (B) has a melt flow rate (230° C., 2.16 kg load) of 30 to 300 g / 10 min. Requirement (B-iii): The intrinsic viscosity [η] of the propylene-α-olefin copolymer part (b-2) measured in o-dichlorobenzene at 135°C is 1.0 to 7.0 dl / g. Requirement (X-ii): The polypropylene composition (X) contains 5 to 50% by weight of a propylene-based polymer (A1) and 50 to 95% by weight of a propylene-based polymer (B) (provided that the total of the propylene-based polymer (Aa) and the propylene-based polymer (B) is 100% by weight).
[0011] In addition, according to a fourth aspect of the present invention, there is provided a polypropylene resin composition according to any one of the first to third aspects of the present invention, wherein the biomass filler (D) is at least one plant-derived filler selected from the group consisting of wood, pulp, cellulose fiber, bamboo, sugarcane (bagasse), rice husks, and rice (starch).
[0012] Further, according to a fifth aspect of the present invention, there is provided the polypropylene resin composition in any one of the first to fourth aspects of the present invention, wherein the biomass filler (D) has an average particle size of 5 to 300 μm.
[0013] In addition, according to a sixth aspect of the present invention, there is provided a polypropylene resin composition according to any one of the first to fifth aspects of the present invention, wherein the compatibilizer (C) is at least one modified polyolefin selected from the group consisting of acid-modified polyolefins and hydroxy-modified polyolefins.
[0014] According to a seventh aspect of the present invention, there is provided an injection-molded article made of the polypropylene resin composition according to any one of the first to sixth aspects of the present invention. Effect of the Invention
[0015] The polypropylene resin composition of the present invention is less susceptible to discoloration due to fading of the biomass filler, and has excellent injection moldability and molded appearance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention relates to a polypropylene resin composition comprising a specific polypropylene composition (X), a compatibilizer (C) and a biomass filler (D) in specific ratios, and a molded article thereof. The components used in the present invention, and the resulting polypropylene resin composition and molded article will be described in detail below.
[0017] 0. Polypropylene composition (X) The polypropylene composition (X) used in the present invention satisfies the following requirement (Xi). Requirement (Xi): The polypropylene composition (X) contains a propylene polymer (A) that satisfies the following requirements (Ai) to (A-ii).
[0018] The polypropylene composition (X) preferably satisfies the following requirement (X-ii). Requirement (X-ii): The polypropylene composition (X) contains 5 to 50% by weight of a propylene-α-olefin block copolymer (A1) and 50 to 95% by weight of a propylene-based polymer (B) (provided that the total of the propylene-α-olefin block copolymer (A1) and the propylene-based polymer (B) is 100% by weight).
[0019] 1. Propylene-based polymer (A) The propylene polymer (A) used in the present invention satisfies the following requirements (Ai) to (A-ii). Requirement (Ai): The propylene polymer (A) contains a propylene / α-olefin block copolymer (A1) satisfying the requirements (A1-i) to (A1-iii). Requirement (A-ii): The propylene polymer (A) has a melt flow rate (230° C., 2.16 kg load) of 1.0 to 200 g / 10 min.
[0020] The propylene-α-olefin block copolymer (A1) satisfies the following requirements (A1-i) to (A1-iii): Requirement (A1-i): The propylene / α-olefin block copolymer (A1) contains a propylene homopolymer portion (a1-1) and a propylene / α-olefin copolymer portion (a1-2), and the propylene homopolymer portion (a1-1) is 50 to 95% by weight and the propylene / α-olefin copolymer portion (a1-2) is 5 to 50% by weight (however, the total of the propylene homopolymer portion (a1-1) and the propylene / α-olefin copolymer portion (a1-2) is 100% by weight). Requirement (A1-ii): The propylene content of the propylene-α-olefin copolymer part (a1-2) is 30 to 80% by weight, and the α-olefin content is 20 to 70% by weight (with the proviso that the total of the propylene content and the α-olefin content is 100% by weight). Requirement (A1-iii): The intrinsic viscosity [η] of the propylene-α-olefin copolymer portion (a1-2) measured in o-dichlorobenzene at 135°C is 7.0 to 12.0 dl / g or less.
[0021] The propylene polymer (A) used in the present invention may contain, in addition to the propylene / α-olefin block copolymer (A1), a propylene homopolymer, a propylene / α-olefin random copolymer, or a propylene / α-olefin block copolymer, within the range not impairing the effects of the present invention.
[0022] The polypropylene composition (X) contains a propylene / α-olefin block copolymer (A), and preferably contains a propylene-based polymer (B) satisfying the following requirements (Bi) to (B-iii) as the other propylene / α-olefin block copolymer. In this case, the polypropylene composition (X) preferably further satisfies the following requirement (X-ii). Requirement (Bi): The propylene polymer (B) is a propylene-α-olefin block copolymer containing a propylene homopolymer portion (b-1) and a propylene-α-olefin copolymer portion (b-2). Requirement (B-ii): The propylene polymer (B) has a melt flow rate (230° C., 2.16 kg load) of 30 to 300 g / 10 min. Requirement (B-iii): The intrinsic viscosity [η] of the propylene-α-olefin copolymer part (b-2) measured in o-dichlorobenzene at 135°C is 1.0 to 7.0 dl / g. Requirement (X-ii): The polypropylene composition (X) contains 5 to 50% by weight of a propylene-based polymer (A1) and 50 to 95% by weight of a propylene-based polymer (B) (provided that the total of the propylene-based polymer (A1) and the propylene-based polymer (B) is 100% by weight).
[0023] Each of these will be explained in detail below.
[0024] I. Propylene-α-olefin block copolymer (A1) The propylene / α-olefin block copolymer (A1) satisfies the above-mentioned requirements (A1-i) to (A1-iii).
[0025] Requirement (A1-i): Propylene homopolymer portion (a1-1) and propylene-α-olefin copolymer portion (a1-2) The propylene / α-olefin block copolymer (A1) contains a propylene homopolymer portion (a1-1) and a propylene / α-olefin copolymer portion (a1-2). The propylene / α-olefin block copolymer (A1) used here is usually obtained by sequential polymerization.
[0026] The content of the propylene homopolymer portion (a1-1) in the propylene / α-olefin block copolymer (A1) is 50-95% by weight, preferably 60-90% by weight, and more preferably 70-85% by weight (wherein the total of the propylene homopolymer portion (a1-1) and the propylene / α-olefin copolymer portion (a1-2) is 100% by weight). If the content of the propylene homopolymer portion (a1-1) is less than 50% by weight, the rigidity of the molded article may decrease. If it exceeds 95% by weight, the molded article may have noticeable flow marks, resulting in poor appearance. On the other hand, the content of the propylene / α-olefin copolymer portion (a1-2) is 5-50% by weight, preferably 10-40% by weight, and more preferably 15-30% by weight. By setting the content of the propylene / α-olefin copolymer portion (a1-2) in such a range, the flow marks of the molded article are not noticeable, the appearance is good, and the rigidity of the molded article can be maintained at a good level. That is, if the content of the propylene / α-olefin copolymer portion (a1-2) is less than 5% by weight, the flow marks of the molded article may be noticeable, resulting in poor appearance. On the other hand, if it exceeds 50% by weight, the rigidity of the molded article may decrease.
[0027] Examples of the α-olefins used in the propylene-α-olefin block copolymer (A1) include ethylene, 1-butene, 2-methyl-1-propene, 1-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 2-ethyl-1-butene, 2,3-dimethyl-1-butene, 2-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, 1-heptene, methyl-1-hexene, dimethyl-1-pentene, ethyl-1-pentene, trimethyl-1-butene, and 1-octene. These may be copolymerized using one type, or may be copolymerized in combination of two or more types. Among them, from the viewpoint of improving the impact strength of the molded article, ethylene or 1-butene, which have a large effect, are preferred, and ethylene and ethylene-1-butene blocks are most preferred.
[0028] Requirement (A1-ii): Propylene content and α-olefin content of the propylene-α-olefin copolymer portion (a1-2) The propylene content of the propylene-α-olefin copolymer portion (a1-2) is 30 to 80% by weight, preferably 40 to 70% by weight, and more preferably 50 to 65% by weight. By setting the propylene content of the propylene-α-olefin copolymer portion (a1-2) in this range, it is possible to maintain the impact resistance of the molded article in a good range. In other words, if the content is outside the above range, the impact resistance of the molded article may not be sufficient. On the other hand, the α-olefin content of the propylene-α-olefin copolymer portion (a1-2) is 20 to 70% by weight, preferably 30 to 60% by weight, and more preferably 35 to 50% by weight. By setting the propylene content of the propylene-α-olefin copolymer portion (a1-2) in this range, it is possible to maintain the impact resistance of the molded article in a good range. In other words, if the content is outside the above range, the impact resistance of the molded article may not be sufficient. The propylene content of the propylene-α-olefin copolymer portion (a1-2) is a value measured using a cross fractionation device, FT-IR, or the like, and the measurement conditions and the like may be those described in, for example, JP-A-2008-189893.
[0029] Requirement (A1-iii): Intrinsic viscosity [η] of the propylene-α-olefin copolymer part (a1-2) measured in o-dichlorobenzene at 135°C The intrinsic viscosity [η] of the propylene-α-olefin copolymer part (a1-2) measured in o-dichlorobenzene at 135°C is 7.0 to 12.0 dl / g, preferably 8.0 to 11.0 dl / g or more, more preferably 9.0 to 10.0 dl / g. By setting the intrinsic viscosity [η] in such a range, the flow mark improvement effect due to high normal stress can be sufficiently obtained, and bright spots do not occur, and a good molded appearance can be obtained. That is, if the intrinsic viscosity [η] is less than 7.0 dl / g, the flow mark improvement effect due to high normal stress may not be sufficiently obtained. Also, if the intrinsic viscosity [η] exceeds 12.0 dl / g, poor dispersion of the propylene-α-olefin copolymer part (a1-2) may occur during production, resulting in poor molded appearance such as bright spots. The intrinsic viscosity [η] can be measured by dissolving the propylene polymer (A) in p-xylene at 130°C to prepare a solution, leaving the solution at 25°C for 12 hours, filtering off the precipitated polymer, evaporating p-xylene from the filtrate to obtain the propylene-α-olefin copolymer part (a1-2), and then using orthodichlorobenzene as a solvent and an Ubbelohde viscometer at a temperature of 135°C.
[0030] In a preferred embodiment of the present invention, the propylene / α-olefin block copolymer (A1) is at least one selected from the group consisting of a propylene / ethylene block copolymer and a propylene / ethylene / 1-butene block copolymer. When the propylene / α-olefin block copolymer (A1) is at least one selected from the group, the effect of improving the impact strength of the molded article is large.
[0031] II. Method for producing propylene-α-olefin block copolymer (A1) The propylene-α-olefin block copolymer (A1) is not particularly limited in the manufacturing method as long as it satisfies the above-mentioned requirements (A1-i) to (A1-iii), but as described above, it is a mixture of a propylene homopolymer portion (a1-1) and a propylene-α-olefin copolymer portion (a1-2) that satisfies a high intrinsic viscosity [η]. This is obtained by a manufacturing process including polymerization of the propylene homopolymer portion (a1-1) (first stage polymerization) followed by polymerization of the propylene-α-olefin copolymer portion (a1-2) (second stage polymerization). Examples of such a method include the methods disclosed in JP-A-2004-18647, JP-A-2007-284668, and JP-A-2015-025124.
[0032] The propylene homopolymer portion (a1-1) is produced in one or more polymerization stages (reaction conditions for each stage may be the same or different), and the propylene / α-olefin copolymer portion (a1-2) is also produced in one or more polymerization stages (reaction conditions for each stage may be the same or different). Thus, the entire production process for the propylene / α-olefin block copolymer (A1) used in the present invention is a sequential multi-stage polymerization process of at least two stages.
[0033] The polymerization may be carried out in a batch, semi-batch or continuous manner, but the continuous manner is industrially preferred. Possible polymerization modes include slurry polymerization using an inert hydrocarbon such as hexane, heptane, octane, benzene, or toluene as a polymerization solvent, bulk polymerization using propylene itself as a polymerization solvent, and gas phase polymerization in which the raw material propylene is polymerized in a gas phase state. It is also possible to carry out a combination of these polymerization modes.
[0034] For example, there may be mentioned a method in which the first stage polymerization is carried out by bulk polymerization and the second stage polymerization is carried out by gas phase polymerization, a method in which the first stage polymerization is carried out by gas phase polymerization and the second stage polymerization is carried out by gas phase polymerization, or a method in which the first stage polymerization is carried out by bulk polymerization and subsequent gas phase polymerization and the second stage polymerization is carried out by gas phase polymerization. In the present invention, since the propylene-α-olefin copolymer portion (a1-2) during polymerization has a relatively high ethylene concentration, propylene is difficult to liquefy, and the pressure must be increased to carry out bulk polymerization. Therefore, slurry polymerization and gas phase polymerization are preferred. More preferably, the first stage polymerization is carried out in a gas phase first reactor, and the second stage polymerization is carried out in a gas phase second reactor.
[0035] The polymerization reactor may be of any shape or structure, and may include a reactor equipped with an agitator, which is generally used in slurry polymerization and bulk polymerization, a tubular reactor, a fluidized bed reactor, which is generally used in gas phase polymerization, and a horizontal reactor having an agitator blade. Fluidized bed reactors and horizontal reactors having an agitator blade are preferred because they are easy to control the activity when producing a crystalline propylene polymer. In particular, a fluidized bed reactor is more preferred because a wide range of operating conditions can be adopted.
[0036] In a preferred embodiment of the present invention, the first reactor and the second reactor are fluidized bed reactors, or the first reactor and the second reactor are horizontal reactors having an agitator blade.
[0037] The type of polymerization catalyst used in the production of the propylene-α-olefin block copolymer (A1) is not particularly limited, and known catalysts can be used. For example, so-called Ziegler-Natta catalysts, which combine titanium compounds and organoaluminum, or metallocene catalysts (see, for example, JP-A-5-295022) can be used. The higher the intrinsic viscosity (higher the molecular weight) of the propylene-ethylene random copolymer, the greater the effect of improving the appearance when added, so Ziegler-Natta catalysts, which generally have less chain transfer reactions during polymerization and are easy to increase the molecular weight, are preferred.
[0038] Ziegler-Natta catalysts include those obtained by treating titanium trichloride or titanium trichloride compositions obtained by reduction with organoaluminum or the like as a titanium compound with an electron donor compound for further activation (see, for example, JP-A-47-34478, JP-A-58-23806, and JP-A-63-146906), and so-called supported catalysts obtained by supporting titanium tetrachloride on a carrier such as magnesium chloride (see, for example, JP-A-58-157808, JP-A-58-83006, JP-A-58-5310, and JP-A-61-218606).
[0039] In addition, an organic aluminum compound is used as a cocatalyst. For example, trialkyl aluminum such as trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, etc., alkyl aluminum halide such as diethyl aluminum chloride, diisobutyl aluminum chloride, etc., alkyl aluminum hydride such as diethyl aluminum hydride, alkyl aluminum alkoxide such as diethyl aluminum ethoxide, alumoxane such as methyl alumoxane, tetrabutyl alumoxane, etc., complex organic aluminum compound such as dibutyl methylboronate, lithium aluminum tetraethyl, etc. can be used in combination of two or more kinds.
[0040] Since the organoaluminum compound used as a cocatalyst also acts as a chain transfer agent during polymerization, it is preferable to use it at a concentration as low as possible so as not to inhibit the activity of the cocatalyst. Specifically, it is preferable to adjust the amount of organoaluminum used so that the aluminum atom concentration of the powder present in the reactor is 30 to 80 ppm during the polymerization of the propylene-ethylene random copolymer portion (later stage).
[0041] In addition, various polymerization additives can be used for the catalyst for the purpose of improving stereoregularity, controlling particle properties, controlling the amount of solvent-soluble components, controlling molecular weight distribution, etc. Examples of the electron donor compounds include organosilicon compounds such as diphenyldimethoxysilane and tert-butylmethyldimethoxysilane, esters such as ethyl acetate, butyl benzoate, methyl p-toluate, and dibutyl phthalate, ketones such as acetone and methyl isobutyl ketone, ethers such as diethyl ether, organic acids such as benzoic acid and propionic acid, and alcohols such as ethanol and butanol.
[0042] In the polymerization (first-stage polymerization) of the propylene homopolymer portion (a1-1), propylene and, if necessary, a chain transfer agent such as hydrogen are supplied to a reactor, and propylene is polymerized in the presence of a polymerization catalyst under conditions of, for example, a temperature of 50 to 150°C, preferably 50 to 70°C, a propylene partial pressure of 0.5 to 4.5 MPa, preferably 1.0 to 3.0 MPa, and an average residence time of the powder present in the reactor of 0.5 to 5.0 Hr, to produce a crystalline propylene polymer portion. The propylene homopolymer portion (a1-1) may be copolymerized with an α-olefin other than propylene, for example, less than 0.5% by weight of ethylene when the α-olefin is ethylene, within the range not impairing the effects of the present invention.
[0043] The melt flow rate (hereinafter sometimes abbreviated as MFR) of the propylene homopolymer portion (a1-1) (230°C, 2.16 kg load) is usually in the range of 5 to 500 g / 10 min, preferably 10 to 450 g / 10 min, and more preferably 300 to 400 g / 10 min. In order to make the propylene homopolymer portion (a1-1) of the propylene-α-olefin block copolymer (A1) fall within such a range, the hydrogen of the chain transfer agent is preferably in the range of 5×10 in terms of hydrogen / propylene molar ratio, although this may vary depending on the type of catalyst. -3 By performing the process within the range of 0.2 to 1.0, it is possible to adjust the MFR to a desired value.
[0044] In this specification, the melt flow rate (230°C, 2.16 kg load) is a value measured in accordance with JIS K7210:1999 "Testing method for melt mass flow rate (MFR) and melt volume flow rate (MVR) of plastics - thermoplastics", Method A, Condition M (230°C, 2.16 kg load).
[0045] Subsequently, polymerization of the propylene-α-olefin copolymer portion (a1-2) (second-stage polymerization) is carried out by supplying propylene, an α-olefin, a chain transfer agent such as hydrogen, etc. to a reactor, and random copolymerization of propylene and an α-olefin is carried out in the presence of the polymerization catalyst (the catalyst used in the first-stage polymerization) under conditions such as a temperature of 50 to 150°C, preferably 50 to 90°C, partial pressures of propylene and α-olefin of 0.3 to 4.5 MPa, preferably 0.5 to 3.5 MPa, respectively, and an average residence time of the powder retained in the reactor of 1.0 to 7.0 Hr to produce the propylene-α-olefin copolymer portion (a1-2), thereby obtaining the propylene-α-olefin block copolymer (A1) as the final product. Examples of α-olefins include ethylene, 1-butene, 2-methyl-1-propene, 1-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 2-ethyl-1-butene, 2,3-dimethyl-1-butene, 2-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, 1-heptene, methyl-1-hexene, dimethyl-1-pentene, ethyl-1-pentene, trimethyl-1-butene, and 1-octene. These may be copolymerized using one type, or may be copolymerized using a combination of two or more types. Among them, from the viewpoint of improving the impact strength of molded products, ethylene or 1-butene, which have a large effect, are preferred, and ethylene is the most preferred.
[0046] In this case, since the intrinsic viscosity [η] of the propylene-α-olefin copolymer portion (a1-2) in the propylene-α-olefin block copolymer (A1) needs to be 7.0 to 12.0 dl / g, it is preferable to adjust the concentration of a chain transfer agent such as hydrogen to a relatively low level, although this depends on the process and the type of catalyst.
[0047] During the production of the propylene-α-olefin copolymer part (a1-2), a chain transfer agent may or may not be present, but it is preferable to have a small amount of chain transfer agent present in order to adjust the intrinsic viscosity [η] of the resulting propylene-α-olefin copolymer part (a1-2) to a range in which flow marks are reduced and bright spots do not occur, resulting in a good molded appearance. If there is too much chain transfer agent, [η] will decrease, and there is a risk that the effect of reducing flow marks will not be obtained. On the other hand, if there is too little chain transfer agent, [η] will increase, and poor dispersion of the propylene-α-olefin copolymer part (a1-2) will occur, which may result in poor molded appearance, such as bright spots.
[0048] When hydrogen is used as the chain transfer agent, the molar ratio of hydrogen to propylene in the second reactor is preferably 0.00001 to 0.05, more preferably 0.0001 to 0.001.
[0049] As described above, the MFR of the propylene-α-olefin block copolymer (A1) is usually in the range of 1.0 to 200 g / 10 min, and the MFR (230°C, 2.16 kg load) of the propylene homopolymer portion (a1-1) is usually in the range of 5 to 500 g / 10 min., so the MFR (230°C, 2.16 kg load) of the propylene-α-olefin copolymer portion (a1-2) is 1.0 × 10 -4 A concentration of up to 10 g / 10 min is preferable because it provides the effects of the present invention and also provides good moldability. The MFR of the propylene-α-olefin copolymer part (a1-2) is 1×10 -4 To control the reaction rate to 10g / 10min, the hydrogen / (propylene + α-olefin) molar ratio should be set to 1×10 -5By performing the process within the range of 0.8 to 1.0, it is possible to adjust the MFR to a desired value.
[0050] Furthermore, in order to prevent the occurrence of bright spots, which are believed to be caused by poor dispersion of the propylene-α-olefin copolymer portion (a1-2), it is preferable to charge alcohol after the polymerization in the first polymerization step and during the polymerization in the second polymerization step. The amount of alcohol to be charged is preferably a 1.0 to 2.0 mol ratio (alcohol / organoaluminum) to the amount of organoaluminum charged in the first polymerization step.
[0051] That is, the molar ratio (alcohol / organoaluminum) of the alcohol supplied to the second reactor to the organoaluminum supplied to the first reactor is preferably 1.0 to 2.0. Examples of the alcohol include methyl alcohol, ethyl alcohol, n-propyl alcohol, and i-propyl alcohol.
[0052] III. Propylene-based polymer (B) The polypropylene composition (X) used in the present invention preferably contains a propylene polymer (B) satisfying the following requirements (Bi) to (B-iii). Requirement (Bi): The propylene polymer (B) is a propylene-α-olefin block copolymer containing a propylene homopolymer portion (b-1) and a propylene-α-olefin copolymer portion (b-2). Requirement (B-ii): The propylene polymer (B) has a melt flow rate (230° C., 2.16 kg load) of 30 to 300 g / 10 min. Requirement (B-iii): The intrinsic viscosity [η] of the propylene-α-olefin copolymer part (b-2) measured in o-dichlorobenzene at 135°C is 1.0 to 7.0 dl / g.
[0053] Requirement (Bi): Propylene homopolymer portion (b-1) and propylene-α-olefin copolymer portion (b-2) The propylene polymer (B) comprises a propylene homopolymer portion (b-1) and a propylene-α-olefin copolymer portion (b-2), and the propylene polymer (B) used here is usually obtained by sequential polymerization. The content of the propylene homopolymer part (b-1) in the propylene polymer (B) is 50 to 95% by weight, preferably 60 to 90% by weight, and more preferably 70 to 85% by weight (wherein the total of the propylene homopolymer part (b-1) and the propylene-α-olefin copolymer part (b-2) is 100% by weight). By setting the content of the propylene homopolymer part (b-1) in this range, it is possible to maintain the rigidity and impact resistance of the molded article in a good range. That is, if the content of the propylene homopolymer part (b-1) is less than 50% by weight, the rigidity of the molded article may decrease. On the other hand, if it exceeds 95% by weight, the impact resistance of the molded article may decrease. On the other hand, the content of the propylene / α-olefin copolymer portion (b-2) is 5-50% by weight, preferably 10-40% by weight, and more preferably 15-30% by weight (wherein the total of the propylene homopolymer portion (b-1) and the propylene / α-olefin copolymer portion (b-2) is 100% by weight). By setting the content of the propylene homopolymer portion (b-2) within such a range, it becomes possible to maintain the rigidity and impact resistance of the molded article within a good range. That is, if the content of the propylene / α-olefin copolymer portion (b-2) is less than 5% by weight, the impact resistance of the molded article may decrease. On the other hand, if it exceeds 50% by weight, the rigidity of the molded article may decrease.
[0054] Examples of the α-olefins used in the propylene-based polymer (B) include ethylene, 1-butene, 2-methyl-1-propene, 1-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 2-ethyl-1-butene, 2,3-dimethyl-1-butene, 2-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, 1-heptene, methyl-1-hexene, dimethyl-1-pentene, ethyl-1-pentene, trimethyl-1-butene, and 1-octene. These may be copolymerized using one type, or may be copolymerized using a combination of two or more types. Among them, from the viewpoint of improving the impact strength of the molded article, ethylene or 1-butene, which have a large effect, are preferred, and ethylene and ethylene-1-butene blocks are most preferred.
[0055] The propylene content of the propylene-α-olefin copolymer part (b-2) is 30-90% by weight, preferably 40-80% by weight, and more preferably 50-75% by weight (the sum of the propylene content and the α-olefin content is 100% by weight). By setting the propylene content of the propylene-α-olefin copolymer part (b-2) in this range, it is possible to maintain the impact resistance of the molded article in a good range. In other words, if the content is outside the above range, the impact resistance of the molded article may not be sufficient. On the other hand, the α-olefin content of the propylene-α-olefin copolymer part (b-2) is 10-70% by weight, preferably 20-60% by weight, and more preferably 25-50% by weight (the sum of the propylene content and the α-olefin content is 100% by weight). By setting the α-olefin content of the propylene-α-olefin copolymer part (b-2) within this range, it is possible to maintain the impact resistance of the molded article within a good range. In other words, if the content is outside the above range, the impact resistance of the molded article may not be sufficient.
[0056] Requirement (B-ii): Melt flow rate of propylene polymer (B) The melt flow rate of the propylene polymer (B) (230°C, 2.16 kg load) is usually 30 to 300 g / 10 min, preferably 40 to 200 g / 10 min, more preferably 50 to 150 g / 10 min. By setting the melt flow rate of the propylene polymer (B) in such a range, the fluidity of the polypropylene resin composition of the present invention is improved, the filling rate of the material during dispersion of the biomass filler and injection molding is improved, and discoloration of the biomass filler and deterioration of odor due to shear heat do not occur, and the impact resistance of the molded product does not decrease and the molded product does not become sticky due to low molecular weight components. That is, if the melt flow rate is less than 30 g / 10 min, the fluidity of the polypropylene resin composition of the present invention decreases, and there is a risk of poor dispersion of the biomass filler, molding defects due to a decrease in the filling rate of the material in injection molding, discoloration of the biomass filler and deterioration of odor due to shear heat, etc. On the other hand, if the melt flow rate exceeds 300 g / 10 min, the impact resistance of the molded article may decrease and the molded article may become sticky due to low molecular weight components.
[0057] Requirement (B-iii): Intrinsic viscosity [η] of the propylene-α-olefin copolymer part (b-2) measured in o-dichlorobenzene at 135°C The intrinsic viscosity [η] of the propylene-α-olefin copolymer part (b-2) measured in o-dichlorobenzene at 135°C is 1.0 to 7.0 dl / g, preferably 1.5 to 5.0 dl / g, more preferably 2.0 to 4.0 dl / g. By setting the intrinsic viscosity [η] in such a range, the impact resistance of the molded product can be set in a good range, and it is possible to maintain appropriate productivity without unnecessarily lengthening the polymerization time during production. That is, if the intrinsic viscosity [η] is less than 1.0 dl / g, the impact resistance of the molded product may decrease. On the other hand, if the intrinsic viscosity [η] exceeds 7.0 dl / g, the time required for polymerization may increase, and the productivity may decrease.
[0058] IV. Method for producing propylene polymer (B) The method for producing the propylene polymer (B) contained in the polypropylene composition (X) used in the present invention will be described below.
[0059] The propylene polymer (B) used in the present invention is preferably produced by a polymerization method using a highly stereoregular catalyst. The propylene-α-olefin block copolymer is a reaction mixture of a propylene homopolymer portion (b-1) and a propylene-α-olefin copolymer portion (b-2). This is obtained by a production process of polymerization of the propylene homopolymer portion (b-1), which is a crystalline propylene polymer portion (first step), followed by polymerization of the propylene-α-olefin copolymer portion (b-2) (second step).
[0060] The catalyst used in the polymerization is not particularly limited as long as it is a catalyst with high stereoregularity, and as described above, known catalysts can be used. For example, so-called Ziegler-Natta catalysts combining titanium compounds and organoaluminum (for example, as described in Polypropylene Handbook (first edition, first printing published May 15, 1998)) or metallocene catalysts (for example, see JP-A-5-295022) can be used. Ziegler-Natta catalysts include those obtained by treating titanium trichloride or titanium trichloride compositions obtained by reduction with organoaluminum or the like as a titanium compound with an electron donor compound for further activation (see, for example, JP-A-47-34478, JP-A-58-23806, and JP-A-63-146906), and so-called supported catalysts obtained by supporting titanium tetrachloride on a carrier such as magnesium chloride (see, for example, JP-A-58-157808, JP-A-58-83006, JP-A-58-5310, and JP-A-61-218606).
[0061] Examples of the organoaluminum compound used as a promoter include trialkylaluminum such as trimethylaluminum, triethylaluminum, and triisobutylaluminum, alkylaluminum halides such as diethylaluminum chloride and diisobutylaluminum chloride, alkylaluminum hydrides such as diethylaluminum hydride, alkylaluminum alkoxides such as diethylaluminum ethoxide, alumoxanes such as methylalumoxane and tetrabutylalumoxane, complex organoaluminum compounds such as dibutyl methylboronate and lithiumaluminum tetraethyl, etc. Two or more of these can also be used in combination. In addition, various polymerization additives can be used for the above catalysts for the purpose of improving stereoregularity, controlling particle properties, controlling soluble components, controlling molecular weight distribution, etc. Examples of such additives include electron donor compounds such as organosilicon compounds such as diphenyldimethoxysilane and tert-butylmethyldimethoxysilane, esters such as ethyl acetate, butyl benzoate, methyl p-toluate and dibutyl phthalate, ketones such as acetone and methyl isobutyl ketone, ethers such as diethyl ether, organic acids such as benzoic acid and propionic acid, and alcohols such as ethanol and butanol.
[0062] The polymerization method is as described above, but it can also be slurry polymerization using an inert hydrocarbon such as hexane, heptane, octane, benzene or toluene as a polymerization solvent, bulk polymerization using propylene itself as a polymerization solvent, or gas phase polymerization in which the raw material propylene is polymerized in a gas phase state. It is also possible to combine any of the polymerization methods. For example, the propylene homopolymer part (b-1) can be produced by bulk polymerization, and the propylene-α-olefin copolymer part (b-2) can be produced by gas phase polymerization, or the propylene homopolymer part (b-1) can be produced by bulk polymerization, followed by gas phase polymerization, and the propylene-α-olefin copolymer part (b-2) can be produced by gas phase polymerization. The polymerization may be carried out in a batch, continuous or semi-batch manner, and if desired, a multi-stage, such as two-stage or three-stage, continuous polymerization method may be used. Furthermore, the polymerization reactor may be of any shape or structure, and examples thereof include a tank equipped with a stirrer that is generally used in slurry polymerization or bulk polymerization, a tubular reactor, a fluidized bed reactor that is generally used in gas phase polymerization, and a horizontal reactor equipped with an agitator.
[0063] In the gas phase polymerization, the polymerization step of the propylene homopolymer part (b-1) is carried out by supplying propylene and hydrogen as a chain transfer agent in the presence of the catalyst at a temperature of 0 to 100°C, preferably 30 to 90°C, particularly preferably 40 to 80°C, a propylene partial pressure of 0.6 to 4.2 MPa, preferably 1.0 to 3.5 MPa, particularly preferably 1.5 to 3.0 MPa, and a residence time of 0.5 to 10 hours. The propylene homopolymer part (b-1) may be copolymerized with an α-olefin other than propylene, for example, less than 0.5% by weight of ethylene when the α-olefin is ethylene, within a range that does not impair the effects of the present invention.
[0064] The MFR (230°C, 2.16 kg load) of the propylene homopolymer portion (b-1) of the propylene-based polymer (B) used in the present invention is usually in the range of 0.1 to 50 g / 10 min. In order to make the propylene homopolymer portion (b-1) of the propylene-α-olefin block copolymer in such a range, the hydrogen of the chain transfer agent is preferably in a hydrogen / propylene molar ratio of 5×10 to 5×10, depending on the type of catalyst. -3 By performing the process within the range of 0.2 to 1.0, it is possible to adjust the MFR to a desired value.
[0065] Subsequently, that is, in the presence of the propylene homopolymer part (b-1) produced in the first polymerization step, in the second polymerization step, propylene, α-olefin and hydrogen are supplied to copolymerize propylene and α-olefin in the presence of the catalyst (the catalyst used in the production of the propylene homopolymer part (b-1)) at 0 to 100°C, preferably 30 to 90°C, particularly preferably 40 to 80°C, with partial pressures of propylene and α-olefin of 0.1 to 2.0 MPa, preferably 0.1 to 1.5 MPa, and a residence time of 0.5 to 10 hours, to produce a propylene-α-olefin copolymer part (b-2), and obtain a propylene-based polymer (B) as a final product. In the propylene-α-olefin copolymer portion (b-2), propylene may be copolymerized with two or more kinds of α-olefins within the range that does not impair the effects of the present invention.
[0066] The MFR of the propylene polymer (B) used in the present invention is usually 30 to 300 g / 10 min, as described above. As described above, the MFR of the propylene homopolymer portion (b-1) is usually in the range of 0.1 to 50 g / 10 min., and therefore, in order to set the MFR of the propylene-α-olefin block copolymer in this range, it is preferable that the MFR of the propylene homopolymer portion (b-1) is 40 to 400 g / 10 min. and the MFR of the propylene-α-olefin copolymer portion (b-2) is 0.1 to 10 g / 10 min. When controlling the MFR of the propylene homopolymer portion (b-1) to 40 to 400 g / 10 min, the hydrogen of the chain transfer agent is added at a molar ratio of hydrogen / propylene of 5×10 -3 By performing the process within the range of 0.3 to 1.5, it is possible to adjust the MFR to a desired value. In addition, when controlling the MFR of the propylene-α-olefin copolymer portion (b-2) to 0.1 to 10 g / 10 min, the hydrogen / (propylene + α-olefin) molar ratio is set to 1×10 -5 By performing the process within the range of 1.0 to 1.0, it is possible to adjust the MFR to the desired value.
[0067] In order to maintain the α-olefin content in the propylene-α-olefin copolymer part (b-2) within a specific range, the α-olefin concentration relative to the propylene concentration in the latter stage may be adjusted.
[0068] Furthermore, in order to prevent gelation or stickiness, it is desirable to add alcohols such as ethanol during or before the reaction of the propylene-α-olefin copolymer part (b-2). Specifically, the reaction can be carried out under conditions of an alcohol / organoaluminum compound molar ratio of 0.5 to 3.0. The proportion of the propylene-α-olefin copolymer part (b-2) in the propylene-α-olefin block copolymer can also be controlled by the amount of alcohol added. In addition, since various companies have put a variety of such propylene-α-olefin block copolymers on the market, it is possible to measure the physical properties of these commercially available products and use the desired one.
[0069] Requirement (A-ii): Melt flow rate of propylene polymer (A) (230°C, 2.16 kg load) The melt flow rate (230°C, 2.16 kg load) of the propylene polymer (A) used in the present invention is the most fundamental factor in the molding of polypropylene. Therefore, the MFR of the propylene polymer (A) used in the present invention is 1.0 to 200 g / 10 min, preferably 5.0 to 150 g / 10 min, more preferably 20.0 to 100 g / 10 min. By setting the MFR in such a range, the fluidity of the polypropylene resin composition of the present invention is in a good range, and it is possible to obtain a good molded product without occurrence of poor dispersion of the biomass filler, molding defects due to a decrease in the filling rate of the material during injection molding, discoloration of the biomass filler due to shear heat, and worsening of odor. That is, if the MFR is less than 1.0 g / 10 min, the fluidity of the polypropylene resin composition of the present invention is reduced, and there is a risk of poor dispersion of the biomass filler, molding defects due to a decrease in the filling rate of the material during injection molding, discoloration of the biomass filler due to shear heat, and worsening of odor.
[0070] A specific method for adjusting the MFR to the above range is to change the amount of hydrogen added during polymerization. Hydrogen acts as a chain transfer agent in the polymerization of propylene, so if the amount of hydrogen added is increased, the MFR increases, and conversely, if the amount added is decreased, the MFR can be decreased. The value of the MFR relative to the hydrogen concentration inside the polymerization tank varies depending on the catalyst used and other polymerization conditions, but it is very easy for a person skilled in the art to grasp the relationship between the hydrogen concentration and the MFR in advance depending on the catalyst type and other polymerization conditions, and adjust the hydrogen concentration to achieve the desired MFR value.
[0071] V. Other resins contained in the polypropylene composition (X) (propylene polymer (C)) The polypropylene composition (X) may contain other resins in addition to the propylene polymer (A) (including the propylene-α-olefin block copolymer (A1)) and the propylene polymer (B). Examples of such resins include propylene homopolymers and propylene-α-olefin random copolymers. The propylene homopolymer and propylene-α-olefin random copolymer (hereinafter also referred to as “propylene polymer (C)”) that can be contained in the polypropylene composition (X) preferably satisfy the following requirements (Ci) to (C-iii). Requirement (Ci): No long chain branching. Requirement (C-ii): The melt flow rate (MFR) at 230°C and a load of 2.16 kg is 0.2 to 10 g / 10 min. Requirement (C-iii): At least one polypropylene-based polymer selected from the group consisting of propylene homopolymers and propylene-α-olefin random copolymers.
[0072] In the case where a propylene-α-olefin random copolymer is used as the propylene-based polymer (C) used in the present invention, examples of the α-olefin include ethylene, 1-butene, 2-methyl-1-propene, 1-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 2-ethyl-1-butene, 2,3-dimethyl-1-butene, 2-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, 1-heptene, methyl-1-hexene, dimethyl-1-pentene, ethyl-1-pentene, trimethyl-1-butene, and 1-octene. These may be copolymerized using one kind, or may be copolymerized in combination of two or more kinds. Among them, from the viewpoint of improving the impact strength of the molded body, ethylene or 1-butene, which have a large effect, are preferable, and ethylene is most preferable.
[0073] In the case of a random copolymer of propylene and ethylene, it preferably contains 90 to 99.5% by weight, more preferably 92 to 99% by weight, of propylene units, and preferably 0.5 to 10% by weight, more preferably 1 to 8% by weight of ethylene units (provided that the total of propylene and ethylene is 100% by weight). By setting the ethylene units in such ranges, it becomes possible to set the impact resistance and rigidity of the molded article in a good range. That is, if the ethylene units are less than 0.5% by weight, the impact strength of the molded article may not be sufficient. On the other hand, if the ethylene units exceed 10% by weight, the rigidity may decrease. The contents of propylene units and ethylene units in the random copolymer of propylene and ethylene can be adjusted by controlling the composition ratio of propylene and ethylene during polymerization of the random copolymer of propylene and ethylene. The propylene content of the random copolymer of propylene and ethylene is a value measured using a cross fractionator or FT-IR, and the measurement conditions may be, for example, those described in JP-A-2008-189893.
[0074] When the propylene polymer (C) is a propylene homopolymer or a propylene-α-olefin random copolymer, the MFR can be adjusted by controlling the hydrogen concentration during polymerization.
[0075] VI. Method for producing propylene polymer (C) The method for producing the propylene polymer (C) will be described below. First, the method for producing the propylene homopolymer will be described.
[0076] (i) Method for producing propylene homopolymer When the propylene polymer (C) used in the present invention is a propylene homopolymer, the propylene homopolymer may be produced in accordance with the production method of the propylene homopolymer portion (a1-1) among the production methods of the propylene-α-olefin block copolymer. The MFR (230° C., 2.16 kg load) of the propylene homopolymer used in the present invention is from 0.05 to 5 g / 10 min, preferably from 0.1 to 3 g / 10 min, and more preferably from 0.3 to 1 g / 10 min. In order to set the MFR of the propylene homopolymer in this range, the hydrogen of the chain transfer agent should be at a molar ratio of hydrogen / propylene of 1×10 -3 By performing the process within the range of 0.2 to 1.0, it is possible to adjust the MFR to a desired value.
[0077] (ii) Method for producing propylene-α-olefin random copolymer When the propylene polymer (C) used in the present invention is a propylene-α-olefin random copolymer, the propylene-α-olefin random copolymer may be produced in a manner similar to the production method of the propylene homopolymer part (a1-1) among the above-mentioned production methods of the propylene-α-olefin block copolymer, in which the propylene homopolymer part (a1-1) is copolymerized with an α-olefin other than propylene, preferably with ethylene as an α-olefin. The MFR (230° C., 2.16 kg load) of the propylene / α-olefin random copolymer used in the present invention is 0.05 to 5 g / 10 min, preferably 0.1 to 3 g / 10 min, and more preferably 0.3 to 1 g / 10 min. In order to set the MFR of the propylene-α-olefin random copolymer in this range, the hydrogen of the chain transfer agent is added at a hydrogen / (propylene + α-olefin) molar ratio of 1×10 -5 By performing the process within the range of 0.8 to 1.0, it is possible to adjust the MFR to a desired value.
[0078] 3. Compatibilizer (C) The polypropylene resin composition of the present invention contains a compatibilizer (C) in order to further improve the impact strength and rigidity.
[0079] In one preferred embodiment of the present invention, the compatibilizer (C) is at least one modified polyolefin selected from the group consisting of acid-modified polyolefins and hydroxy-modified polyolefins. When the compatibilizer (C) is at least one selected from this group, the dispersibility of the biomass filler can be further improved. In addition, when the compatibilizer (C) is at least one selected from this group, it has the characteristic of imparting functions such as mechanical properties (particularly rigidity) to a higher degree.
[0080] The acid-modified polyolefin is not particularly limited, and any of the conventionally known polyolefins can be used. The acid-modified polyolefin is, for example, a modified polyolefin such as polyethylene, polypropylene, ethylene-α-olefin copolymer, ethylene-α-olefin-non-conjugated diene compound copolymer (EPDM, etc.), or ethylene-aromatic monovinyl compound-conjugated diene compound copolymer rubber, which is graft-copolymerized with an unsaturated carboxylic acid such as maleic acid or maleic anhydride. The graft copolymerization is carried out, for example, by reacting the polyolefin with an unsaturated carboxylic acid in a suitable solvent using a radical generator such as benzoyl peroxide. The unsaturated carboxylic acid or its derivative can also be introduced into the polymer chain by random or block copolymerization with a polyolefin monomer.
[0081] Examples of unsaturated carboxylic acids used for modification include compounds having a carboxyl group, such as maleic acid, fumaric acid, itaconic acid, acrylic acid, and methacrylic acid, and a polymerizable double bond into which a functional group, such as a hydroxyl group or an amino group, has been introduced as necessary. Derivatives of unsaturated carboxylic acids include their acid anhydrides, esters, amides, imides, and metal salts, and specific examples thereof include maleic anhydride, itaconic anhydride, methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, maleic acid monoethyl ester, maleic acid diethyl ester, fumaric acid monomethyl ester, fumaric acid dimethyl ester, acrylamide, methacrylamide, maleic acid monoamide, maleic acid diamide, fumaric acid monoamide, maleimide, N-butylmaleimide, and sodium methacrylate. Preferred is maleic anhydride.
[0082] The grafting reaction conditions include, for example, dialkyl peroxides such as di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, t-butyl peroxyacetate, t-butyl peroxybenzoate, t-butylperoxyisopropyl carbonate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, An example of a method is to use about 0.001 to 10 parts by weight of an organic peroxide, such as a peroxy ester such as 2,5-dimethyl-2,5-di(benzoylperoxy)hexyne-3, a diacyl peroxide such as benzoyl peroxide, or a hydroperoxide such as diisopropylbenzene hydroperoxide or 2,5-dimethyl-2,5-di(hydroperoxy)hexane, per 100 parts by weight of the polyolefin, and react the organic peroxide in a molten state or in a solution state at a temperature of about 80 to 300°C. The amount of acid modification (sometimes referred to as graft ratio) of the acid-modified polyolefin is not particularly limited, but the amount of acid modification is preferably 0.05 to 10% by weight, more preferably 0.07 to 5% by weight, calculated as maleic anhydride. A preferred acid-modified polyolefin is maleic anhydride-modified polypropylene.
[0083] The hydroxy-modified polyolefin is a modified polyolefin containing a hydroxyl group. The modified polyolefin may have the hydroxyl group at an appropriate site, for example, at the end of the main chain or in a side chain. Examples of olefin resins constituting the hydroxy-modified polyolefin include homopolymers or copolymers of α-olefins such as ethylene, propylene, butene, 4-methylpentene-1, hexene, octene, nonene, decene, and dodecene, and copolymers of the above-mentioned α-olefins with copolymerizable monomers.
[0084] Preferred examples of hydroxy-modified polyolefins include hydroxy-modified polyethylenes (e.g., low-, medium- or high-density polyethylenes, linear low-density polyethylenes, ultra-high molecular weight polyethylenes, ethylene-(meth)acrylic acid ester copolymers, ethylene-vinyl acetate copolymers, etc.), hydroxy-modified polypropylenes (e.g., polypropylene homopolymers such as isotactic polypropylene, random copolymers of propylene and α-olefins (e.g., ethylene, butene, hexane, etc.), propylene-α-olefin block copolymers, etc.), and hydroxy-modified poly(4-methylpentene-1). Examples of monomers for introducing the reactive group include monomers having a hydroxyl group (e.g., allyl alcohol, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, etc.).
[0085] The amount of modification by the monomer having a hydroxyl group is 0.1 to 20% by weight, preferably 0.5 to 10% by weight, based on the olefin resin. The average molecular weight of the hydroxy-modified polyolefin is not particularly limited. For example, in the case of a low molecular weight system, the hydroxy-modified polyolefin can be obtained by polymerizing a conjugated diene monomer by a known method such as anionic polymerization, hydrolyzing the polymer, and hydrogenating the resulting polymer.
[0086] The hydroxy-modified polyolefin preferably has a hydroxyl value of 1 to 100 mgKOH / g as specified by JIS K 0070. If the hydroxyl value is less than 1 mgKOH / g, the impact strength of the polypropylene resin composition of the present invention and the molded article may be deteriorated, whereas if it exceeds 100 mgKOH / g, moldability may be deteriorated.
[0087] The above compatibilizer (C) may be used alone or in combination of two or more kinds. From the viewpoint of further improving the dispersibility of the biomass filler, however, it is preferable to use polypropylene or propylene-α-olefin copolymer graft-modified with maleic anhydride or hydroxyl groups, and it is more preferable to use polypropylene or propylene-α-olefin copolymer graft-modified with maleic anhydride. Various types of these compatibilizers (C) are commercially available from many companies, and a desired product can be purchased and used from among them.
[0088] The content of the compatibilizer (C) is required to be 0.5 to 20 parts by weight, preferably 0.8 to 10 parts by weight, and more preferably 1.0 to 5 parts by weight, based on 100 parts by weight of the polypropylene composition (X). By setting the content of the compatibilizer (C) within such a range, it is possible to obtain good dispersibility of the biomass filler and mechanical strength, and to make the impact resistance of the molded article good. That is, if the content of the compatibilizer (C) is less than 0.5 parts by weight, there is a risk that good dispersibility of the biomass filler and mechanical strength cannot be obtained. On the other hand, if it is more than 20 parts by weight, there is a risk that the impact resistance of the molded article will be reduced.
[0089] 4. Biomass Filler (D) The biomass filler (D) is an organic resource derived from animals and plants, excluding fossil resources such as petroleum and coal, and is preferably an organic resource derived from plants, excluding fossil resources. Examples of organic resources derived from plants, excluding fossil resources, include lignocellulose-based materials, cellulose-based materials, and starch-based materials.
[0090] Lignocellulosic materials include lignocellulosic fibers and lignocellulosic powders. Specific examples include wood pulp, refiner graft pulp (RGP), paper pulp, waste paper, crushed wood chips, wood flour, and fruit shell powder. Specific examples of wood flour include crushed pine, fir, poplar, bamboo, bagasse, and oil palm trunks, as well as sawdust and sawdust, and fruit shell powder includes crushed fruits such as walnuts, peanuts, and palms.
[0091] Examples of cellulosic materials include alpha fiber flock obtained by treating wood pulp with an alkali and then shredding it mechanically, cotton linters obtained from cottonseeds, cotton flock, rayon flock obtained by shredding rayon, cellulose fiber, and the like.
[0092] There are no particular limitations on the form of these lignocellulosic and cellulosic materials, and fibrous and powdery materials can be used.
[0093] The lignocellulosic material or cellulose material may be an esterified lignocellulosic material or esterified cellulose material obtained by adding a polybasic acid anhydride to a hydroxyl group of a lignocellulosic material or cellulose material, an oligoesterified lignocellulosic material or oligoesterified cellulose material obtained by adding a polybasic acid anhydride and a monoepoxy compound to a hydroxyl group of a lignocellulosic material or cellulose material, or an oligoesterified lignocellulosic material or oligoesterified cellulose material obtained by adding a polybasic acid anhydride and a polyhydric alcohol to a hydroxyl group of a lignocellulosic material or cellulose material.
[0094] Examples of polybasic acid anhydrides include maleic anhydride, succinic anhydride, phthalic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, dichloromaleic anhydride, itaconic anhydride, tetrabromophthalic anhydride, HET anhydride, trimellitic anhydride, pyromellitic anhydride, and the like. Of these, maleic anhydride, succinic anhydride, and phthalic anhydride are particularly preferred because they are industrially advantageous and inexpensive.
[0095] The monoepoxy compound may be any compound containing one epoxy group in the molecule, and examples thereof include phenyl glycidyl ether, allyl glycidyl ether, styrene oxide, octylene oxide, methyl glycidyl ether, butyl glycidyl ether, and cresyl glycidyl ether.
[0096] Examples of polyhydric alcohols include ethylene glycol, propylene glycol, trimethylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, pinacol, hydrobenzoin, benzpinacol, cyclopentane-1,2-diol, cyclohexane-1,2-diol, cyclohexane-1,4-diol, glycerin, and polyethylene glycol 400.
[0097] A typical method for carrying out the esterification involves mixing the polybasic acid anhydride (or the polybasic acid anhydride and the monoepoxy compound, or the polybasic acid anhydride and the polyhydric alcohol) in the presence of a lignocellulosic material or a cellulosic material, and reacting the mixture at a temperature of 60 to 150° C. for 0.5 to 8 hours.
[0098] In the case of the reaction of alternately adding and esterifying the polybasic acid anhydride and the monoepoxy compound to the hydroxyl groups in the lignocellulosic or cellulosic material, the reaction proceeds sufficiently without a catalyst, but a basic catalyst such as sodium carbonate, dimethylbenzylamine, tetramethylammonium chloride, or pyridine may be used to promote the reaction. An addition esterification catalyst may also be used.
[0099] From the viewpoints of ease of use and effectiveness, the molecular weight of the oligomer of the polybasic acid anhydride and the monoepoxy compound is preferably about 20 to 1000 (the degree of polymerization is preferably 5 or less, including 1) which can be liquid.
[0100] The blending amounts of the polybasic acid anhydride and the monoepoxy compound are as follows. First, the polybasic acid anhydride is preferably used in an amount of 5 to 120 parts by mass, more preferably 10 to 100 parts by mass, per 100 parts by mass of dried lignocellulosic or cellulose-based material. The monoepoxy compound is preferably used in an amount of 0.5 to 2.0 equivalents of epoxy groups per equivalent of anhydride acid group of the polybasic acid anhydride used. This is preferable because the content of the lignocellulosic or cellulose-based material is maintained and exudation during hot-press molding is suppressed by using 120 parts by mass or less of the polybasic acid anhydride per 100 parts by mass of dried lignocellulosic or cellulose-based material, and the use of 5 parts by mass or more ensures hot-press fluidity and makes it easier to obtain a uniform molded product.
[0101] In the case of a reaction in which the polybasic acid anhydride and the polyhydric alcohol are alternately added to and esterified with the hydroxyl groups of a lignocellulosic or cellulosic material, the monoepoxy compound may be replaced with the polyhydric alcohol.
[0102] Specific examples of starch-based materials include rice, wheat, corn, sugarcane, potato, sweet potato, tapioca, corn starch, potato starch, potato starch, tapioca starch, and lightly acetylated products thereof. Any agricultural product containing starch can be used without being limited to these. These starch-based materials can be used in the general state when stockpiled, or after simple pretreatment such as washing, removing parts that do not contain starch such as the husk, and cutting into appropriate sizes. Starch-based materials are usually obtained in granular form, and can be used as they are.
[0103] Furthermore, it is more preferable that the starch-based material used as the raw material is subjected to such a simple pretreatment and then to a gelatinization treatment as described below. The starch constituting the starch-based material initially has a crystalline structure (β structure), but when heated in the presence of an appropriate amount of water or a hydrophilic plasticizer such as glycerin, this β structure breaks down and changes to an amorphous structure (α structure). In this way, the change from β structure to α structure caused by heating raw starch containing hydrophilic components is called gelatinization. Compared to when the starch grains had a β structure, the starch grains exhibiting this α structure are easily dissolved at the molecular level of the starch in the thermally flowing polypropylene resin and are easily dispersed finely and uniformly.
[0104] It is preferable that trehalose is dissolved in the hydrophilic plasticizer used to convert starch having a β structure to an α structure. The effect of this is that, for example, when rice is used as the starch-based material, the trehalose acts to suppress the decomposition of the lipid components of the rice by impregnating raw rice with an aqueous trehalose solution, and the deterioration over time of the polypropylene resin composition produced using the rice is suppressed. The reason for this is said to be that trehalose has the effect of coating the rice components and protecting the fatty acids from oxidative decomposition.
[0105] Such an effect is not limited to rice, but can also be exhibited by general starch-based materials, and examples of materials having such an effect include, in addition to the above-mentioned trehalose, salt, sucrose, antioxidants, protein decomposition promoters, cellulosic decomposition promoters, etc. By adding these substances to a hydrophilic plasticizer to form an α-structure in the starch-based material, the effect of preventing the characteristic odor, scorching, and coloring of the produced polypropylene resin composition can also be obtained.
[0106] So far, we have explained that starch-based materials that have already been gelatinized are used as raw materials, but by using the production method described below, starch-based materials having a β structure that contain moisture can also be used.
[0107] Specifically, raw rice is soaked in water for a predetermined time, drained, and then put into a kneader together with polypropylene resin and kneaded at the thermal flow temperature of the polypropylene resin. This thermal flow temperature (usually 100 to 170°C) is sufficient to transition the starch structure of raw rice from β structure to α structure, so the raw rice is gelatinized during the kneading process. After the raw rice is converted to α structure in this way, as already mentioned above, the molecular chains of the starch are loosened, refined, and dispersed in the matrix of the polypropylene resin.
[0108] Here, in order for raw rice with a β structure to be heated and turn into an α structure, it is desirable for the water content to be 17% by mass or more, and for this purpose, it is preferable to soak the rice in water for 5 minutes or more. Also, for starch-based materials such as potatoes, which contain enough water to turn the starch into an α structure by themselves, there is no need to soak the potatoes in water like rice, and they can be put into the kneader as they are.
[0109] The biomass filler (D) is preferably one or more plant-derived fillers selected from the group consisting of wood, pulp, cellulose fiber, bamboo, sugarcane (bagasse), rice husk, and rice (starch).
[0110] The biomass filler (D) has an average particle size of preferably 5 to 300 μm, more preferably 10 to 200 μm. When the average particle size is within the above range, secondary aggregation due to a small average particle size during kneading is unlikely to occur, and deterioration of physical properties and moldability is prevented. Also, when the average particle size is within the above range, the occurrence of holes during extrusion molding or thermoforming due to a large average particle size is prevented.
[0111] Here, the average particle size is a value measured using a laser diffraction particle size distribution analyzer, and refers to a value at which the integrated value of the volume accumulation distribution is 50%. An example of the measuring device is a laser method particle size distribution analyzer "LA960" manufactured by Horiba, Ltd.
[0112] The biomass filler (D) is 3 to 150 parts by weight, preferably 4 to 100 parts by weight, more preferably 5 to 30 parts by weight, and even more preferably 6 to 10 parts by weight, per 100 parts by weight of the propylene-based polymer (A). By setting the biomass filler (D) within such a range, the rigidity of the molded article is kept in a good range, and the dispersibility of the biomass filler and the effect of improving flow marks are good. That is, if the biomass filler (D) is less than 3 parts by weight, the rigidity of the molded article may not be sufficient. On the other hand, if it exceeds 150 parts by weight, the dispersibility of the biomass filler and the effect of improving flow marks may not be sufficient.
[0113] 5. Elastomer (E) If necessary, an elastomer (E) can be added to the polypropylene resin composition of the present invention, for example, for the purpose of further improving the effect of impact resistance, within a range that does not significantly impair the effects of the present invention. Examples of the elastomer (E) include olefin-based elastomers and styrene-based elastomers, and from the viewpoints of impact improvement effect and material costs, olefin-based elastomers, particularly ethylene-α-olefin copolymers, are preferred.
[0114] Examples of olefin-based elastomers include ethylene-α-olefin copolymer elastomers such as ethylene-propylene copolymer elastomer (EPR), ethylene-butene copolymer elastomer (EBR), ethylene-hexene copolymer elastomer (EHR), and ethylene-octene copolymer elastomer (EOR); and ethylene-α-olefin-diene terpolymer elastomers such as ethylene-propylene-ethylidenenorbornene copolymer, ethylene-propylene-butadiene copolymer, and ethylene-propylene-isoprene copolymer. Specific examples include those commercially available under the trade name DYNARON (registered trademark) from JSR Corporation, under the trade name TAFUMER (registered trademark) from Mitsui Chemicals, Inc., under the trade names ENGAGE (registered trademark), AFFINITY (registered trademark), and VERSIFY (registered trademark) from The Dow Chemical Company, Ltd., under the trade name Kernel from Japan Polyethylene Corporation, and under the trade name Vistamaxx (registered trademark) from ExxonMobil Chemical Corporation. Among these, ethylene-propylene copolymer elastomers (EPR), ethylene-butene copolymer elastomers (EBR), ethylene-hexene copolymer elastomers (EHR), and ethylene-octene copolymer elastomers (EOR) are preferred.
[0115] Examples of styrene-based elastomers include styrene-butadiene-styrene triblock copolymer elastomer (SBS), styrene-isoprene-styrene triblock copolymer elastomer (SIS), styrene-ethylene-butylene copolymer elastomer (SEB), styrene-ethylene-propylene copolymer elastomer (SEP), styrene-ethylene-butylene-styrene copolymer elastomer (SEBS), styrene-ethylene-butylene-ethylene copolymer elastomer (SEBC), hydrogenated styrene-butadiene elastomer (HSBR), styrene-ethylene Examples of the elastomer include styrene-based elastomers such as styrene-propylene-styrene copolymer elastomer (SEPS), styrene-ethylene-ethylene-propylene-styrene copolymer elastomer (SEEPS), styrene-butadiene-butylene-styrene copolymer elastomer (SBBS), partially hydrogenated styrene-isoprene-styrene copolymer elastomer, partially hydrogenated styrene-isoprene-butadiene-styrene copolymer elastomer, and hydrogenated polymer-based elastomers such as ethylene-ethylene-butylene-ethylene copolymer elastomer (CEBC). Specific examples include those commercially available under the trade names Dynaron (registered trademark) and JSR SIS (registered trademark) from JSR Corporation, Hybra (registered trademark) and Septon (registered trademark) from Kuraray Co., Ltd., Tuftec (registered trademark) from Asahi Kasei Corporation, Sibstar (registered trademark) from Kaneka Corporation, and Kraton (registered trademark) and Kraton D (registered trademark) from Shell Corporation. These elastomers may be used alone or in combination of two or more. Various types of these elastomers (E) are commercially available from many companies, so that a desired product can be purchased and used.
[0116] 6. Fillers other than biomass fillers (F) If necessary, a filler (F) other than the biofiller can be added to the polypropylene resin composition of the present invention, for example, for the purpose of further improving rigidity, within a range that does not significantly impair the effects of the present invention.
[0117] The filler (F) other than the biomass filler may be either an inorganic filler or an organic filler. The inorganic filler and the organic filler may be in the form of particles, plates, rods, whiskers, or fibers.
[0118] Examples of inorganic fillers include oxides such as silica, diatomaceous earth, barium ferrite, beryllium oxide, pumice, and pumice balloon; hydroxides such as aluminum hydroxide, magnesium hydroxide, and basic magnesium carbonate; carbonates such as calcium carbonate, magnesium carbonate, dolomite, and dawsonite; sulfates or sulfites such as calcium sulfate, barium sulfate, ammonium sulfate, and calcium sulfite; talc, clay, mica, glass fibers, glass balloons, glass beads, calcium silicate, wollastonite, montmorillonite, and bentonite; carbons such as carbon black, graphite, carbon fibers, and hollow carbon spheres; molybdenum sulfide, boron fibers, zinc borate, barium metaborate, calcium borate, sodium borate, basic magnesium sulfate fibers, potassium titanate fibers, aluminum borate fibers, calcium silicate fibers, calcium carbonate fibers, and various metal fibers.
[0119] The organic filler is made from fossil resources such as petroleum and coal, and examples of the organic filler include various synthetic fibers such as aromatic polyamide fibers, cellulose fibers, nylon fibers, polyester fibers, and polypropylene fibers, and thermosetting resin powders.
[0120] The filler (F) other than the biomass filler may be surface-treated with an organic titanate coupling agent, an organic silane coupling agent, an unsaturated carboxylic acid or a modified polyolefin grafted with an anhydride thereof, a fatty acid, a fatty acid metal salt, a fatty acid ester, or the like, or may be surface-treated with a combination of two or more of these.
[0121] The filler (F) other than the above biomass filler may be used alone or in a mixture of two or more kinds. However, it is preferable that the filler is at least one selected from talc, glass fiber, carbon fiber, and organic fiber, which can further improve the rigidity of the resin composition and is economical.
[0122] 7.Optional addition ingredients In the polypropylene resin composition of the present invention, in addition to the polypropylene composition (X), the propylene-based polymer (A), and the filler other than biomass filler (F), any additive component may be further blended, if necessary, within a range that does not significantly impair the effects of the present invention, for example, for the purpose of further improving the effects of the present invention or imparting other effects.
[0123] Specific examples of the additives include colorants such as pigments, flowability improving assistants such as waxes, light stabilizers such as hindered amines, ultraviolet absorbers such as benzotriazoles, nucleating agents such as sorbitols, antioxidants such as phenols and phosphorus, nonionic antistatic agents, neutralizing agents such as inorganic compounds, antibacterial and antifungal agents such as thiazoles, flame retardants such as halogen compounds, plasticizers, dispersants such as organic metal salts, lubricants such as fatty acid amides, metal deactivators such as nitrogen compounds, nonionic surfactants, and thermoplastic resins such as polyolefin resins, polyamide resins, and polyester resins other than the propylene polymer (A) and the propylene polymer (B). These optional added components may be used in combination of two or more kinds, may be added to the polypropylene resin composition, or may be added to the propylene-based polymer (A) and the propylene-based polymer (B), etc., and two or more kinds of each component may also be used in combination. Furthermore, since various products of these optional added components are commercially available from many companies, a desired product can be purchased and used from among them.
[0124] Colorants such as inorganic or organic pigments are effective in imparting or improving the colored appearance, appearance, texture, commercial value, weather resistance, durability, etc. of polypropylene resin compositions and molded articles thereof. Specific examples of inorganic pigments include carbon black such as furnace carbon and ketjen carbon; titanium oxide; iron oxide (e.g., red iron oxide); chromic acid (e.g., yellow lead); molybdic acid; selenide sulfide; and ferrocyanide. Specific examples of organic pigments include azo pigments such as sparingly soluble azo lake, soluble azo lake, insoluble azo chelate, condensed azo chelate, and other azo chelates; phthalocyanine pigments such as phthalocyanine blue and phthalocyanine green; anthraquinone, perinone, perylene, and threne pigments such as thioindigo; dye lake; quinacridone; dioxazine; and isoindolinone. In order to achieve a metallic or pearlescent look, aluminum flakes and pearl pigments can be added. Dyes can also be added.
[0125] As the flowability improving assistant, for example, rosin-based resins, petroleum resins and terpene-based resins improve the flowability of the polypropylene resin composition when melted, and are therefore effective in improving moldability. Specific examples of rosin-based resins include Pinus massoniana, Pinus elliottii, Pinus merkusii, Pinus caribaea, Pinus kesiya, Pinus taeda, and Pinus tschonoskii. palustris) and the like, refined rosins (natural rosins and refined rosins are collectively called unmodified rosins), hydrogenated rosins, disproportionated rosins, polymerized rosins, α,β-unsaturated carboxylic acid modified rosins, esters of these rosins (also called rosin esters), rosin phenolic resins, and rosin diols. Petroleum resins include aliphatic petroleum resins, alicyclic petroleum resins, aromatic petroleum resins, aliphatic / aromatic petroleum resins, hydroxyl group-containing petroleum resins, and hydrogenated products thereof (these hydrogenated products are called hydrogenated petroleum resins). Terpene resins include terpene resins, aromatic modified terpene resins, terpene phenolic resins, hydrogenated terpene phenolic resins, and the like.
[0126] Light stabilizers and ultraviolet absorbers, for example, hindered amine compounds, benzotriazoles, benzophenones, and salicylates, are effective in imparting or improving weather resistance, durability, and the like to polypropylene resin compositions and molded articles thereof, and are effective in further improving weather discoloration resistance. Specific examples of the hindered amine compound include condensation products of dimethyl succinate and 1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine; poly[[6-(1,1,3,3-tetramethylbutyl)imino-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidyl)imino]hexamethylene[(2,2,6,6-tetramethyl-4-piperidyl)imino]]; tetrakis(2,2,6,6-tetramethyl-4-piperidyl)1,2,3,4-butane tetracarboxylate; tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)1,2,3,4-butane tetracarboxylate; bis(1,2,2,6,6-pentamethyi-4-piperidyl) 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)-5-chlorobenzotriazole; 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)-5-chlorobenzotriazole; 2-hydroxy-4-methoxybenzophenone; 2-hydroxy-4-n-octoxybenzophenone; and the like. Examples of the salicylate include 4-t-butylphenyl salicylate; 2,4-di-t-butylphenyl 3',5'-di-t-butyl-4'-hydroxybenzoate; and the like. Here, the method of using the light stabilizer and the ultraviolet absorber in combination is preferable because it has a large effect of improving weather resistance, durability, weather discoloration resistance, and the like.
[0127] Antioxidants such as phenol-based, phosphorus-based and sulfur-based antioxidants are effective in imparting or improving heat resistance, processing stability, heat aging resistance, etc. to polypropylene resin compositions and molded articles thereof. Furthermore, antistatic agents such as nonionic and cationic antistatic agents are effective in imparting and improving antistatic properties to polypropylene resin compositions and molded articles thereof.
[0128] 8. Polypropylene resin composition and molded products thereof (1)Characteristics The polypropylene resin composition and molded article thereof of the present invention are less susceptible to discoloration due to fading of the biomass filler, and are excellent in moldability and molded appearance. Specifically, they have the following properties: (i) Melt Flow Rate (MFR) The MFR of the polypropylene resin composition of the present invention is 10 to 100 g / 10 min, preferably 15 to 50 g / 10 min, more preferably 20 to 40 g / 10 min. By setting the MFR in such a range, the impact resistance of the molded product is in a good range, and it is possible to prevent poor dispersion of the biomass filler, molding defects due to a decrease in the filling rate of the material in injection molding, discoloration and odor deterioration due to burning of the biomass filler due to shear heat, etc. That is, if the MFR is less than 10 g / min, there is a risk of poor dispersion of the biomass filler, molding defects due to a decrease in the filling rate of the material in injection molding, discoloration and odor deterioration due to burning of the biomass filler due to shear heat, etc. On the other hand, if it exceeds 100 g / min, there is a risk of the impact resistance of the molded product decreasing.
[0129] (2) Method for producing polypropylene resin composition The polypropylene resin composition of the present invention can be produced by mixing and melt-kneading the polypropylene composition (X) containing the propylene polymer (A), the compatibilizer (C), the biomass filler (D), and, if necessary, the elastomer (E), the filler other than the biomass filler (F) and any optional additional components in the above-mentioned blending ratio by a conventionally known method.
[0130] The mixing is usually carried out using a mixing machine such as a tumbler, a V blender, a ribbon blender, etc., and the melt kneading is usually carried out using a kneading machine such as a single screw extruder, a twin screw extruder, a gelation mixer, a Banbury mixer, a roll mixer, a Brabender plastograph, a kneader, etc., and then the melt kneading and granulation are carried out. When producing by melt kneading and granulation, the blend of the above-mentioned components may be kneaded simultaneously, or each component may be kneaded separately in order to improve performance, that is, for example, a method in which a part or all of the polypropylene composition (X) containing the propylene polymer (A), the compatibilizer (C), and the biomass filler (D) are kneaded first, and then the remaining components are kneaded and granulated can be adopted.
[0131] The melt kneading can be generally carried out using a kneading machine such as a single screw extruder, a twin screw extruder, a gelation mixer, a Banbury mixer, a roll mixer, a Brabender plastograph, or a kneader, followed by granulation. Among these, the melt kneading in a gelation mixer and the melt kneading in a twin-screw extruder in which the polypropylene composition (X) containing the propylene-based polymer (A) and the compatibilizer (C) are thoroughly melt-kneaded together, and then the biomass filler (D) is fed by a side feed method or the like are preferred because they provide good dispersibility of the biomass filler.
[0132] (3) Manufacturing method of injection molded products The injection-molded article of the present invention can be obtained by injection molding the polypropylene resin composition produced by the above-mentioned method, for example, by a well-known injection molding method (including gas-assisted injection molding, two-color injection molding, insert injection molding, core-back injection molding, and sandwich injection molding).
[0133] (4)Applications The polypropylene resin composition of the present invention and its injection-molded articles can be effectively used for, for example, automotive interior and exterior materials, chassis and housing for home appliances, civil engineering and construction materials, agricultural, dairy and fishery materials, industrial materials such as food containers and containers, daily necessities such as trash cans, recreational materials, and sports materials.
[0134] The polypropylene resin composition of the present invention is also suitably used in the fields of electrical insulating materials, industrial parts and materials, building materials, etc., and is particularly suitably used as a raw material for housing components, building materials, and home appliances. Specific examples include trays, tableware, speakers, bathroom unit floor pans, buckets, toilet seats, cabinets, stereo cabinets, baseboards, door materials, counter materials, window frames, soundproofing boards, shelves, civil engineering square timber, pillars, structural materials, kitchen components, floors, bathrooms, underlayment boards, piano organ main boards, building fixture ceiling materials, etc. EXAMPLES
[0135] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples. The evaluation methods, analytical methods and materials used in the examples are as follows.
[0136] 1. Evaluation and analysis methods (1) Melt flow rate (MFR) (unit: g / 10 min): Measured in accordance with JIS-K7210 at 230°C and a load of 2.16 kg (load of 21.18 N). (2) Hue (YI value) The hue (YI value) of the pellets and the injection molded test pieces was determined at an ambient temperature of 23°C using a colorimeter "ZE 6000" manufactured by Nippon Denshoku Industries Co., Ltd., in accordance with JIS K-7373. The hue (YI value) was determined according to the following criteria, with the more positive the value, the more yellow the color, and the more negative the value, the more blue the color. Note that the larger the positive YI value, the more yellow the color due to discoloration of the biomass filler caused by fading, etc. Note that the larger the positive YI value, the more yellow the color due to discoloration of the biomass filler caused by fading, etc. ◎: YI value is 0 or more and less than 25 ○: YI value is 25 or more and less than 40 △: YI value is 40 or more and less than 55 ×: YI value is 55 or more The pellets used in the measurement were obtained by melt kneading in the blending ratio shown in Table 2 below. The injection-molded test pieces used in the measurements were obtained by molding the above pellets using an injection molding machine EC30SXII manufactured by Shibaura Machine Co., Ltd. under the following conditions: molding temperature 200°C, mold temperature 40°C, injection speed 52 mm / sec, injection pressure 40 MPa, injection time 8 seconds, and cooling time 12 seconds, resulting in injection-molded test pieces with a thickness of 2.0 mm, width 40.0 mm, and length 80.0 mm. (2) Propylene-α-olefin copolymer portion, α-olefin content This was determined by a combination of the cross-fractionation method and FT-IR method described in JP 2017-031359 A. (3) Measurement of intrinsic viscosity [η] The intrinsic viscosity [η] of the propylene / α-olefin copolymer part in the present invention was measured by the following method. 2g of propylene-based polymer was dissolved in 300mL of p-xylene (containing 0.5mg / mL of BHT) at 130℃ to obtain a solution, which was then left to stand at 25℃ for 12 hours. The precipitated polymer was then filtered off, p-xylene was evaporated from the filtrate, and the solution was dried under reduced pressure at 100℃ for 12 hours to obtain a propylene-α-olefin copolymer part (a1-2 (propylene-based polymer (B) is described as (b-2))). The viscosity was then measured using an Ubbelohde viscometer at 135℃ using orthodichlorobenzene as a solvent (unit: dl / g). (4) Density: Using injection-molded test pieces with a thickness of 4.0 mm, width of 10.0 mm, and length of 80.0 mm, measurements were performed in accordance with JIS K7112 at an ambient temperature of 23°C (units are g / cm 3 ). The test pieces were molded using an injection molding machine EC100SX-2A manufactured by Shibaura Machine Co., Ltd. under conditions of a molding temperature of 200°C and a mold temperature of 40°C. (5)Flexural modulus: Using injection-molded test pieces with a thickness of 4.0 mm, width of 10.0 mm, and length of 80.0 mm, measurements were taken in accordance with JIS K7171 at an atmospheric temperature of 23°C (units are MPa). The test pieces were molded in the same manner as for the above density. (6) Bending stress: Using injection-molded test pieces with a thickness of 4.0 mm, width of 10.0 mm, and length of 80.0 mm, measurements were taken in accordance with JIS K7171 at an atmospheric temperature of 23°C (units are MPa). The test pieces were molded in the same manner as for the above density. (7) Charpy impact strength: In accordance with JIS K 7144, a notch (notch tip radius 0.25 mm ± 0.05 mm) was cut into an injection-molded test piece having a thickness of 4.0 mm, width of 10.0 mm, and length of 80.0 mm. Measurements were performed in accordance with JIS K 7111-1 at an ambient temperature of 23°C (units are kJ / m 2 ). The test pieces were molded in the same manner as for the above density. (8) Number of biomass filler aggregates: Using a pressed test piece having a thickness of 1.0 mm, a width of 100.0 mm, and a length of 100.0 mm, the number of biomass filler aggregates of 0.4 mm or more was visually counted and evaluated according to the following criteria. ◎: Number of aggregates: 0 or more, but less than 20 ○: Number of aggregates is 20 or more and less than 40 △: Number of aggregates is 40 or more and less than 100 ×: 100 or more aggregates The test pieces were molded using a small test press "mini TEST PRESS·10" manufactured by Toyo Seiki Seisakusho. After preheating at a molding temperature of 200°C and 0 MPa for 7 minutes, the pieces were pressed at 4 MPa for 3 minutes, and then cooled at 30°C and 15 MPa for 2 minutes. (9) Flow mark appearance: Using an SE220HD injection molding machine manufactured by Sumitomo Heavy Industries, Ltd., a mold having a film gate with a width of 2 mm on the short side was used to injection mold a molded sheet having dimensions of 350.0 mm x 100.0 mm x 2.0 mmt at a molding temperature of 200° C., a mold temperature of 40° C. The occurrence of flow marks on the mirror surface was visually observed, the distance from the gate to the part where the flow marks occurred was measured, and the occurrence was judged according to the following criteria A to C. A: The distance to the part where the flow mark occurred is 100.0 mm or more. B: The distance to the part where the flow mark occurred is 50.0 mm or more and less than 100.0 mm C: The distance to the part where the flow mark occurred is less than 50.0 mm The appearance of flow marks was evaluated according to the following criteria as a comprehensive evaluation of the four molded sheets each rated A to C. ××: More than one of the four sheets were rated C, and the sheet was extremely poor. ×: None of the above ratings are applicable, but there is one rating of C, which means it is defective and not suitable for practical use. △: Not applicable to the above "XX" or "X" evaluations, less than half of the four sheets measured were rated A, and the sheet is good and usable. ◯: None of the above evaluations apply, and the majority of the four sheets measured were rated A, which means that the sheet is very good. Table 2 shows the average distance to the location where flow marks occurred for the four molded sheets.
[0137] 2.Material (1) Propylene-α-olefin block copolymer (A1) <Production Example 1 of Propylene-α-Olefin Block Copolymer> 1. Catalyst Preparation A 10-liter autoclave equipped with a stirrer was thoroughly purged with nitrogen, and 2 liters of purified toluene was introduced. 200 g of diethoxymagnesium Mg(OEt)2 and 1 liter of titanium tetrachloride were added to this at room temperature. The temperature was raised to 90°C, and 50 ml of n-butyl phthalate was introduced. The temperature was then raised to 110°C, and the reaction was carried out for 3 hours. The reaction product was thoroughly washed with purified toluene.
[0138] Next, refined toluene was introduced to adjust the total liquid volume to 2 L. 1 L of titanium tetrachloride was added at room temperature, and the temperature was raised to 110° C. to carry out the reaction for 2 hours. The reaction product was thoroughly washed with refined toluene.
[0139] Furthermore, the toluene was replaced with n-heptane using purified n-heptane to obtain a slurry of the solid catalyst component. A part of this slurry was sampled and dried. Analysis revealed that the titanium content of the solid catalyst component was 2.7% by weight and the magnesium content was 18% by weight. The average particle size of the solid catalyst component was 33 μm.
[0140] Next, a 20-liter autoclave equipped with a stirrer was thoroughly purged with nitrogen, and 100 g of the slurry of the solid catalyst component (catalyst 1-1) was introduced as the solid catalyst component (catalyst 1-1). Purified n-heptane was introduced to adjust the concentration of the solid catalyst component (catalyst 1-1) to 25 g / liter. 50 mL of silicon tetrachloride SiCl4 was added, and the reaction was carried out at 90°C for 1 hour. The reaction product was thoroughly washed with purified n-heptane.
[0141] After that, refined n-heptane was introduced to adjust the liquid level to 4 liters. 30 ml of dimethyldivinylsilane, 30 ml of t-butylmethyldimethoxysilane (t-C4H9)(CH3)Si(OCH3)2, and 80 g of n-heptane diluted triethylaluminum Et3Al (as Et3Al) were added and reacted at 40°C for 2 hours. The reaction product was thoroughly washed with refined n-heptane, and a portion of the resulting slurry was sampled and dried. Analysis showed that the solid components contained 1.2 wt% titanium and 8.8 wt% (t-C4H9)(CH3)Si(OCH3)2.
[0142] The solid component obtained above was used to carry out preliminary polymerization according to the following procedure. Purified n-heptane was introduced into the above slurry to adjust the concentration of the solid component to 20 g / L. After cooling the slurry to 10°C, 10 g of n-heptane diluted triethylaluminum Et3Al was added as Et3Al, and 280 g of propylene was fed over 4 hours.
[0143] After the supply of propylene was completed, the reaction was continued for another 30 minutes. The gas phase was then thoroughly replaced with nitrogen, and the reaction product was thoroughly washed with purified n-heptane. The resulting slurry was extracted from the autoclave and vacuum dried to obtain a solid catalyst component (catalyst 1). This solid catalyst component (catalyst 1) contained 2.5 g of polypropylene per 1 g of solid component. Analysis revealed that the portion of the solid catalyst component (catalyst 1) excluding polypropylene contained 1.0 wt% titanium and 8.2 wt% (t-C4H9)(CH3)Si(OCH3)2.
[0144] 2. Preparation of propylene-ethylene block copolymer Polymerization was carried out using a continuous reactor consisting of two connected fluidized bed reactors with an internal volume of 2000 liters. First, in the first reactor, the polymerization temperature was 58°C, the propylene partial pressure was 1.8 MPa (absolute pressure), hydrogen as a molecular weight control agent was continuously fed so that the hydrogen / propylene molar ratio was 0.035, and triethylaluminum was fed at 4.0 g / hr and the above-mentioned catalyst 1 was fed so that the polymer polymerization rate was 16 kg / hr. The powder (crystalline propylene polymer) polymerized in the first reactor was continuously withdrawn at a withdrawal rate of 16 kg / hr so that the powder amount in the reactor was 40 kg, and was continuously transferred to the second reactor (first-stage polymerization step).
[0145] In the second reactor, propylene and ethylene were continuously fed to the polymerization temperature of 60°C, the monomer pressure of 1.5MPa, and the ethylene / propylene molar ratio of 0.44. Hydrogen was continuously fed as a molecular weight control agent to the polymerization temperature of 60°C, and ethyl alcohol was fed to the first reactor in an amount of 1.37 times the amount of triethylaluminum fed to the first reactor. The powder polymerized in the second reactor was continuously withdrawn into a vessel so that the powder amount in the reactor was 60 kg. The reaction was stopped by feeding nitrogen gas containing moisture, and a propylene-ethylene block copolymer was obtained (second-stage polymerization process).
[0146] The reaction conditions in the first and second polymerization stages, and the physical properties of the crystalline propylene polymer obtained in the first polymerization stage and the propylene-ethylene random copolymer obtained in the second polymerization stage are shown in Table 1.
[0147] [Table 1]
[0148] To 100 parts by weight of the obtained propylene-ethylene block copolymer powder, 0.1 parts by weight of tetrakis[methylene-3-(3'5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane (Ciba-Geigy, product name: Irganox 1010) as an antioxidant, 0.05 parts by weight of tris(2,4-di-t-butylphenyl)phosphite (Ciba-Geigy, product name: Irgaphos 168) as a neutralizing agent, and 0.15 parts by weight of calcium stearate as a neutralizing agent were added, and mixed and blended for 5 minutes in a Supermixer (Kawada Manufacturing Co., Ltd.). Using the obtained blend, polypropylene granules were obtained by the underwater cutting granulation method under the following equipment and conditions. The obtained granules were used as propylene-α-olefin block copolymer (A1)-1. Kneading extruder: Inner diameter 110 mm single screw extruder Die: TiC, φ2.5, 20 holes, heat channel type Cutter blade: TiC, 4 blades, rake angle 50° Granule processing rate: 200kg / hr Cooling water temperature: 43℃
[0149] (2) Propylene polymer (B) The following propylene polymers, components (B)-1 and (B)-2, were prepared. The properties of these resins are summarized in Table 1. (All of the following are pellets to which antioxidants and neutralizing agents have been added.) Component (B)-1: A grade of "Novatec PP" manufactured by Japan Polypropylene Corporation and having the following composition was used. The material is a propylene-α-olefin block copolymer polymerized with a Ziegler-Natta catalyst, where the α-olefin is ethylene. The MFR (230°C, 2.16 kg load) of the entire copolymer is 100.0 g / 10 min, the content of the propylene-α-olefin copolymer part (component (b-2)) is 20 wt%, the α-olefin content of the propylene-α-olefin copolymer part is 40 wt%, and the intrinsic viscosity [η] of the propylene-α-olefin copolymer part (b-2) is 3 dl / g. Component (B)-2: A grade of "Novatec PP" manufactured by Japan Polypropylene Corporation and having the following composition was used. The material is a propylene-α-olefin block copolymer polymerized with a Ziegler-Natta catalyst, where the α-olefin is ethylene. The MFR (230°C, 2.16 kg load) of the entire copolymer is 16.0 g / 10 min, the content of the propylene-α-olefin copolymer part (component (b-2)) is 17 wt%, the α-olefin content of the propylene-α-olefin copolymer part is 54 wt%, and the intrinsic viscosity [η] of the propylene-α-olefin copolymer part (b-2) is 3 dl / g.
[0150] (3) Compatibilizer (C) As the compatibilizer (C), the following commercially available compatibilizers were used. Component (C)-1: Modic, manufactured by Mitsubishi Chemical Corporation TM P928).
[0151] (4) Biomass filler (D) As the biomass filler (D), the following commercially available biomass fillers were used. Component (D)-1: Product name "KC Flock W100GK" manufactured by Nippon Paper Industries Co., Ltd.
[0152] (5) Elastomer (E) As the elastomer (E), the following commercially available elastomers were used. Component (E)-1: Ethylene-octene random copolymer manufactured by Dow, product name "ENGAGE8200". The MFR of the material (230°C, 2.16 kg load) is 10.0 g / 10 min, and the density is 0.870 g / cm 3 It is.
[0153] (6) Fillers other than biomass fillers (F) As the filler (F) other than the biomass filler, the following commercially available fillers other than the biomass filler were used. Ingredient (F)-1: Manufactured by Nippon Talc Co., Ltd., product name "PC25RC". The median diameter D50 calculated from the particle size value at 50% by weight of cumulative amount read from the particle size cumulative distribution curve measured in accordance with JIS R1629 using a laser method particle size distribution measuring instrument "LA960" manufactured by Horiba, Ltd., is 5 μm.
[0154] 3. Examples and Comparative Examples (1) Production and molding of polypropylene resin composition [Example 1] In the blending ratio shown in Table 2, 100 parts by weight of propylene polymer (A) was mixed with 0.08 parts by weight of a phenol-based antioxidant (Irganox 1010, manufactured by Ciba Specialty Chemicals), 0.08 parts by weight of a phosphorus-based antioxidant (Irgafos 168, manufactured by Ciba Specialty Chemicals), and 0.16 parts by weight of calcium stearate using a super mixer, and then melt-kneaded using the following gelation mixer to obtain a resin. Mixing equipment: Kawata Co., Ltd., product name "SMV-20A" Tank capacity: 20L - Wing type: Upper wing S type, lower wing BL type Blade rotation speed: 2000 rpm Oil temperature control: 200℃ Capacity: 3kg / batch Timing to end mixing: When the resin temperature reaches 180°C. The obtained resin was further melt-kneaded using the following co-rotating intermeshing twin screw extruder and pelletized before use. Mixing equipment: Technovel twin screw extruder, product name "KZW25TW-45MG-NH(900)" L / D=45 Screw speed: 340 rpm Temperature settings: C1, C2~C7, head, die: 180, 200~200, 180, 180℃ Die: Strand die Granule processing rate: 7kg / hr ·Cooling water temperature: 20℃
[0155] [Examples 2 to 5, Comparative Examples 1 to 2] Using the blending ratio shown in Table 2, the same operation as in Example 1 was carried out to obtain pellets.
[0156] (2) Evaluation The obtained pellets were molded into respective test pieces for evaluation in the manner described in the above evaluation method, and the performance was evaluated. The results are shown in Table 2.
[0157] [Table 2]
[0158] Examples 1 to 5, which satisfy the requirements of the invention for the polypropylene resin composition and molded article thereof, show little discoloration due to fading of the biomass filler and are excellent in moldability and appearance of the molded article.
[0159] On the other hand, Comparative Examples 1 and 2, which do not satisfy the requirements of the essential constituent elements of the present invention, are inferior due to a poor balance of these performances. For example, in Comparative Example 1, since the propylene-α-olefin block copolymer (A1) is not contained, discoloration due to scorching of the biomass filler is small, but flow marks occur immediately after the gate, resulting in poor molded appearance compared to Examples 1 and 5. In Comparative Example 2, since the melt flow rate of the pellets of the polypropylene resin composition is 10 g / 10 min or less, discoloration occurs due to scorching of the biomass filler, and flow marks occur immediately after the gate, resulting in poor molded appearance compared to Examples 1 to 5.
[0160] [Industrial Applicability] The polypropylene resin composition of the present invention and molded articles using the same are less susceptible to discoloration due to fading of the biomass filler and have excellent moldability and molded appearance, and therefore can be effectively used for applications such as automotive interior and exterior materials, chassis and housing for home appliances, civil engineering and construction materials, agricultural, dairy farming, and fishery materials, industrial materials such as food containers and containers, daily necessities such as trash cans, recreational materials, and sports materials.
Claims
1. A polypropylene resin composition comprising 0.5 to 20 parts by weight of a compatibilizer (C) and 3 to 150 parts by weight of a biomass filler (D) relative to 100 parts by weight of a polypropylene composition (X) satisfying the following requirement (X-i), and having a melt flow rate (MFR: 230°C, 2.16 kg load) of 10 to 100 g / 10 min. Requirement (Xi): The polypropylene composition (X) contains a propylene polymer (A) which satisfies the following requirements (Ai) to (A-ii). Requirement (Ai): The propylene polymer (A) contains a propylene / α-olefin block copolymer (A1) which satisfies the following requirements (A1-i) to (A1-iii). Requirement (A1-i): The propylene / α-olefin block copolymer (A1) contains a propylene homopolymer portion (a1-1) and a propylene / α-olefin copolymer portion (a1-2), and the propylene homopolymer portion (a1-1) is 50 to 95% by weight and the propylene / α-olefin copolymer portion (a1-2) is 5 to 50% by weight (the total of the propylene homopolymer portion (a1-1) and the propylene / α-olefin copolymer portion (a1-2) is 100% by weight). Requirement (A1-ii): The propylene content of the propylene / α-olefin copolymer portion (a1-2) is 30 to 80% by weight, and the α-olefin content is 20 to 70% by weight (with the proviso that the total of the propylene content and the α-olefin content is 100% by weight). Requirement (A1-iii): The intrinsic viscosity [η] of the propylene / α-olefin copolymer portion (a1-2) measured in o-dichlorobenzene at 135° C. is 7.0 to 12.0 dl / g. Requirement (A-ii): The propylene polymer (A) has a melt flow rate (230° C., 2.16 kg load) of 1.0 to 200 g / 10 min.
2. The polypropylene resin composition according to claim 1, wherein the propylene-α-olefin block copolymer (A1) is at least one selected from the group consisting of a propylene-ethylene block copolymer and a propylene-ethylene-1-butene block copolymer.
3. The polypropylene resin composition according to claim 1, wherein the polypropylene composition (X) further contains a propylene-based polymer (B) satisfying the following requirements (Bi) to (B-iii) and further satisfies the following requirement (X-ii). Requirement (Bi): The propylene polymer (B) is a propylene / α-olefin block copolymer containing a propylene homopolymer portion (b-1) and a propylene / α-olefin copolymer portion (b-2). Requirement (B-ii): The propylene polymer (B) has a melt flow rate (230° C., 2.16 kg load) of 30 to 300 g / 10 min. Requirement (B-iii): The intrinsic viscosity [η] of the propylene / α-olefin copolymer part (b-2) measured in o-dichlorobenzene at 135° C. is 1.0 to 7.0 dl / g. Requirement (X-ii): The polypropylene composition (X) contains 5 to 50% by weight of a propylene-α-olefin block copolymer (A1) and 50 to 95% by weight of a propylene-based polymer (B) (provided that the total of the propylene-α-olefin block copolymer (A1) and the propylene-based polymer (B) is 100% by weight).
4. The polypropylene resin composition according to claim 1, wherein the biomass filler (D) is at least one plant-derived filler selected from the group consisting of wood, pulp, cellulose fiber, bamboo, sugarcane (bagasse), rice husks and rice (starch).
5. The polypropylene resin composition according to claim 1, wherein the biomass filler (D) has an average particle size of 5 to 300 μm.
6. The polypropylene resin composition according to claim 1, wherein the compatibilizer (C) is at least one modified polyolefin selected from the group consisting of acid-modified polyolefins and hydroxy-modified polyolefins.
7. An injection molded article comprising the polypropylene resin composition according to any one of claims 1 to 6.
Citation Information
Patent Citations
Plant-based resin pellet, method for producing the same, and injection molding machine by using the plant-based resin material
JP2011236410A
Resin composition and method for producing the same
JP2023011541A
Resin composition and molded body
JP2023091719A
Woody synthetic resin compositions
WO2003070824A1
Cited By
Bacteriostatic polypropylene-based wood-plastic composite material for vehicles and preparation method thereof
CN121136282A